Advances in the application of neuroinflammatory molecular imaging in brain malignancies - Dong, Wenxia; Wang, Ning; Qi, Zhe (Frontiers in Immunology, 2023)
The prevalence of brain cancer has been increasing in recent decades, posing significant healthcare challenges. The introduction of immunotherapies has brought forth notable diagnostic imaging challenges for brain tumours. The tumour microenvironment undergoes substantial changes in induced immunosuppression and immune responses following the development of primary brain tumour and brain metastasis, affecting the progression and metastasis of brain tumours. Consequently, effective and accurate neuroimaging techniques are necessary for clinical practice and monitoring. However, patients with brain tumours might experience radiation-induced necrosis or other neuroinflammation. Currently, positron emission tomography and various magnetic resonance imaging techniques play a crucial role in diagnosing and evaluating brain tumours. Nevertheless, differentiating between brain tumours and necrotic lesions or inflamed tissues remains a significant challenge in the clinical diagnosis of the advancements in immunotherapeutics and precision oncology have underscored the importance of clinically applicable imaging measures for diagnosing and monitoring neuroinflammation. This review summarises recent advances in neuroimaging methods aimed at enhancing the specificity of brain tumour diagnosis and evaluating inflamed lesions.